Sonographic findings and perinatal outcome of multiple pregnancies associating a complete hydatiform mole and a live fetus: A case series. Issue 8 (28th May 2014) - Kutuk, Mehmet Serdar; Ozgun, Mahmut Tuncay; Dolanbay, Mehmet; Batukan, Cem; Uludag, Semih; Basbug, Mustafa
ABSTRACT Background The aim of this case series was to present the ultrasonographic findings, clinical features, management, and outcome of multiple pregnancies with complete hydatidiform mole and coexisting fetus (CHMCF). Methods Sonographic features and obstetrical and perinatal outcomes of seven cases with CHMCF were analyzed retrospectively. Results A total of seven cases was included in the analysis. Six cases were twins and one case was quadruplet. The mean ± SD maternal age was 25.3 ± 1.9 years (median: 25; range: 23–29). The mean gestational age at diagnosis was 16.1 ± 4.6 weeks (median: 17; range: 11–23). Two pregnancies were achieved by ovulation induction. Two couples opted for pregnancy termination. Four pregnancies resulted in fetal loss between the 11th and 23th week of gestation. One pregnancy ended with the preterm delivery of a live‐born neonate at 34 weeks due to pre‐eclampsia. One patient developed persistent trophoblastic disease, which was treated by hysterectomy. The mean ± SD time for β‐human chorionic gonadotropin clearance was 3.7 ± 0.5 weeks (median: 4; range: 3–4) in the six patients without persistent trophoblastic disease. Conclusions Spontaneous fetal loss is the most likely outcome for CHMCF. However, on the basis of our experience, we recommend carefully monitored continuation of pregnancy as long as maternal complications are not present or are controllable. © 2014 Wiley Periodicals, Inc. J Clin Ultrasound42:465–471, 2014